Seed viability versus seed vigour of canola (Brassica napus L.) cultivars in South Africa and the impact on establishment - Lötter, Devan DeVilliers (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.